Exploring the Association between Obesity, Inflammation, and Type II Diabetes: Insights from Body Mass Index Correlation and Immune Response Analysis - I. Kadhim, Hawraa; Saad Kadhim, Ali (Al-Nahrain Journal of Science, 2024)
Diabetes mellitus (DM) is a group of physiological disorders characterized by a prolonged hyperglycemic state caused by insulin secretion and activity. Recently, several study positive correlations between the increase in BMI and T2D. Additionally, the immune system has contributed to the pathogenicity of T2D in obese individuals. The current study sought to investigate the correlation between obesity and inflammation in obese T2D and obese non-T2D individuals and also detected the role of increasing BMI in obese individuals and developing T2D. The finding involved 100 participants (50 obeseT2D and 50 obese without T2D). The serum of all participants underwent the following immunological and biochemistry tests, which include FBS, Insulin, IAA, ANA, BMI, and HOMA-IR. This study revealed that obese males develop T2D more than females (60.0%, 40.0% respectively) Moreover, Obese T2D and obese without T2D individuals were increased concentrations of IgG in serum levels with markers (ANA, HOMA-IR, and IL-6). While IgG levels in IAA serum were considerably greater in obese T2D individuals only. Furthermore, BMI has been positively associated with an increasing level of ANA, HOMA-IR, and IL-6 in both groups. This investigation unveiled a direct correlation between escalating BMI and the incidence of T2D. Additionally, it revealed the active impact of obesity on the immune response and its consequential contribution to the pathogenesis of T2D.